User experiences of wearable activity monitor among 3-6-year-old preschool children - Are children willing to wear monitor 7 days 24 hours per day? - Suvi Määttä (Frontiers Media S.A., 2015)
Background The reliable and accurate measures of health behaviors are essential when evaluating the effectiveness of behavior change interventions among small children. Self-report methods are not feasible for children whereas direct observation is not practical for measuring large groups of children. Therefore objective methods are preferred over subjective methods for measuring children's health behaviors, such as physical activity (PA) and sleep. Wearable devices among others accelerometers are practical due to their relatively small size and accuracy in measuring quantities of PA and sleep in normal life situations. When selecting the appropriate wearable devices, the characteristics of population studied and research context need to be taken into account. For example, small children have different kind of compliance factors than older children or adults. To be able to measure both PA and sleep, the device needs to be worn 24 hours and in addition, to illustrate the normal habits of PA and sleep, the device is recommend wear 7 days. Little information is however available on the 24-hour acceptability of accelerometer use in small children. Aims This study aimed to explore 3-6-year-old children's compliance to wearing hip-mounted accelerometers. The device acceptability, the compliance of wearing device and barriers to their use that may effect on wearing time were checked. Methods/Results This study was conducted as a part of long-term DAGIS project that aims to improve the health behaviors and diminish socioeconomic inequalities in health behaviors among preschool children in Finland. A large cross-sectional survey is conducted in autumn 2015. Children (N=800, aged 3-6 years) wear Actigraph WGT3X-BT accelerometer for seven days, 24 hours per day. Simultaneously with accelerometer use, parents fill in diary with informing the user experiences of accelerometer and possible non-wearing times. Parents are advised that the child wears accelerometer 24 hours and remove the belt only when in water (e.g. in shower). The accelerometer data are checked straight after data collection. Choi (2011) wear time analyses are conducted for data. The device acceptability, compliance for wearing times and reported barriers for using accelerometer 24 hours in seven days among 3-6-year-old children are reported. Conclusions This study provides new information about the usability of wearable activity monitors among 3-6-year-old children, an age group that is less studied.